Global Power Dynamics: Geopolitical Change in the 21st Century - Kunkunrat Kunkunrat (Jurnal Info Sains : Informatika dan Sains, 2021)
This research aims to understand the dynamics of changes in global power in the geopolitical context of the 21st century. Through a qualitative approach, this research uses case study methodology and cross-country analysis to collect and analyze secondary data from related literature, policy analysis, as well as interviews with geopolitical experts and related stakeholders. The results of this research highlight the shift in political and economic dominance to Asia in the 21st century. The economic revival of countries such as China, South Korea, India and Indonesia confirms that Asia is increasingly becoming the center of attention in global dynamics. The confrontation between the United States and China reflects tensions in efforts to maintain and achieve supremacy at the international level. The formation of the Quad alliance, as a response to China's influence in the Indo-Pacific Region, shows the United States' strategy in managing regional dynamics. The transformation of the roles of the United States and Europe indicates that world power is increasingly dispersed.